Analysis of Students’ Argumentation Skill in Science Learning using Engineering Design Process - Yustika, Devi; Putra, Pramudya Dwi Aristya; Prihatin, Jekti (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2023)
Argumentation skills are very important in science learning which is used to build opinions with rational evidence to draw conclusions through logical reasoning. This research is a qualitative research with a case study approach to identify students' argumentation skills using learning Engineering Design Process (EDP). The subjects of this study were 12 students, each consisting of six male students and six female students in grade 7 junior high school. The data collected are in the form of observation data, documentation and interviews during learning. The collected data will be reduced, analyzed based on indicators of argumentation skills and presented and then drawn conclusions. The results showed that students' argumentation skills in EDP learning were dominated by components claim by 87%, 47% data, and 33% warrant. This shows that students' arguments are not have been good, so they are only able to provide claims without understanding the underlying reasons and the existing data relationships as evidence to support claims. Experience aspects, science concepts, and user needs help students build solution designs during learning. EDP ​​through a collaborative process has helped and expanded students' ideas and arguments in solving problems.